Taking Initiatives: Reconciling Race, Religion, Media and Democracy in the Quest for Marriage Equality - Varona, Anthony E. (Columbia Journal of Gender and Law, 2010)
Election Days 2008 and 2009 proved to be largely disappointing ones for gay rights advocates, and specifically supporters of civil same-sex marriage rights in the United States. Although Election Day 2008 brought the historic civil rights milestone of the election of the first African American president, it also brought with it the passage of statewide ballot initiatives targeting the gay and lesbian minority in four states. Voters stripped gays and lesbians of the civil right to marry in California, after all three branches of state government had affirmed the right and 18,000 Californian same-sex couples had exercised it. Voters also prohibited gays and lesbians from adopting or serving as foster parents in Arkansas, prohibited the civil recognition of same-sex marriage in Arizona and banned both civil same-sex marriage and any “substantially equivalent” relationship in Florida. The Election Day 2009 results were more mixed overall, but no different with respect to same-sex marriage. Maine voters, who had been expected to make the state the first to uphold civil marriage equality through a ballot initiative, ended up voting in favor of a ban. Maine’s defeat of same-sex marriage represented the thirty-first loss at the ballot box for same-sex marriage. By contrast, voters in Washington State approved what was popularly referred to as an “everything but marriage” statute, granting same-sex couples many of the civil benefits of marriage while withholding the right to marry.